Implementasi Hukum Waris Islam pada Rukun Kematian Perumahan Beringin Indah Permai Kelurahan Sungai Beringin (Studi Kasus Kematian pada Tahun 2022) - Akbar, Nasyabandi; Herdiansyah; Ramadhan, Muhammad Fadli; Jabbar, Farhan (Indra Institute Research & Publication, 2024)
The Beringin Indah Permai Housing Association for Death is a community association in the Beringin Indah Permai housing area and its surroundings which was formed to facilitate and assist its members in organizing matters related to death cases. The Beringin Indah Permai Housing Society currently has 153 members, and has entered its second leadership period. This death association is responsible for the process of handling the body when a death occurs in its operational area, starting from washing the body, preparing the shroud, praying for the body, making the coffin, to digging the grave. This research aims to find out how far Islamic inheritance law has been implemented by members at the Beringin Indah Permai Housing Society in 2022. To obtain accurate data, the research was carried out based on deductive descriptive characteristics. This research, which uses empirical sociological methods, succeeded in obtaining data through interview observations and various literature. Referring to the research results, it was found that Islamic inheritance law has not been implemented properly and completely in the scope of death at the Beringin Indah Permai Housing Complex. Most of the distribution of inheritance within the scope of death at Beringin Indah Permai Housing does not use Islamic inheritance law in its implementation